Comparison of Tzanakis Score vs Alvarado Score in the Effective Diagnosis of Acute Appendicitis - Malla, BR; Batajoo, H (Kathmandu University Medical Journal, 2015)
Background Acute appendicitis is the most frequent surgical emergency encountered worldwide. This study was conducted to compare the efficacy of Tzanakis score and Alvarado score in diagnosing acute appendicitis.Objectives The aim of this study is to compare the efficacy of Tzanakis scoring system with Alvarado scoring system in diagnosing AA.Methods This was a retrospective and nonrandomized observational study conducted in Dhulikhel hospital. It included 200 clinically diagnosed cases of acute appendicitis who underwent emergency open or laparoscopic appendectomy during the year 2012. Final diagnosis of acute appendicitis was based on histological findings given by pathologist.Results The sensitivity, specificity, positive predictive value and negative predictive value of Tzanakis score was 86.9%, 75.0, 97.5% and 33.3% respectively. The sensitivity, specificity, positive predictive value and negative predictive value of Alvarado score was 76.0%, 75.0%, 97.2% and 21.4% respectively. Negative appendectomy was 8.0%. Conclusion Tzanakis scoring system is an effective scoring system in diagnosing acute appendicitis.Kathmandu University Medical Journal Vol.12(1) 2014: 48-50